Problem 4: Symmetrical Properties of Roots

Given that α\alpha is a root of the equation x2x+3=0x^2-x+3=0, show that

(a) α3+2α+3=0\alpha^3+2\alpha+3=0

(b) α4+5α2+9=0\alpha^4+5\alpha^2+9=0

#Algebra

Note by Victor Loh
6 years, 10 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

You simply need to show that a^2 - a + 3 is a root for both these equations(used a instead of alpha)

Tanya Gupta - 6 years, 10 months ago

Log in to reply

Is there a more efficient way of doing so? (Hint: Manipulate the given equation)

Victor Loh - 6 years, 10 months ago

multiply by a. plug in value of a^3.

hemang sarkar - 6 years, 10 months ago

Hint: (a) Multiply the first equation by xx. Clearly α\alpha is also a root to this equation. Now we substitute x2x^2 from the original equation.

Exercise: Solve (b)

A Brilliant Member - 6 years, 10 months ago

Since a (using instead of alpha) is a root of x^2 - x + 3 =0 so a satisfies it.hence a^2 - a + 3 =0. Now dividing a^3 + 2a +3 by a^2 - a + 3 we get quotient=a+1& remainder=0. So a^3 +2a+3=(a+1)(a^2 -a+3) + 0 (divident = quotient*divisor + remainder). Since a^2 -a+3=0, so a^3 +2a+3=0.hence the ans.... Similarly we divide a^4 +5a^2 +9 by a^2 -a+3 getting quotient=a^2 +a+3 & remainder =0. Since a^2 -a+3=0 so we get, a^4+ 5a^2 +9 =0...

Ankush Gogoi - 6 years, 10 months ago

a^3+2a+3=a(a^2+2)+3=a(a^2-a+3+a-3+2)+3=a(0+a-1)+3=a^2-a+3=0 similarly second one can be done

A P Rao - 6 years, 6 months ago
×

Problem Loading...

Note Loading...

Set Loading...